Private bank deposits and macro/fiscal risk in the euro-area - Michael G. Arghyrou; Maria Dolores Gadea (Center for Economic Studies and ifo Institute (CESifo), 2019)
We examine the relationship between private bank deposits and macro/fiscal risk in the euro area. We test three hypotheses: First, private bank deposits relative to Germany are determined by macro/fiscal risk factors. Second, this relationship is time-varying. Third, time-variation is driven by the level of macro/fiscal risk. Our findings validate all three tested hypotheses. They also reveal persistent fragmentation between EMU core and periphery banking systems caused by a deficit of trust in periphery banking systems, unmitigated by the introduction of OMT and European Banking Union. Our findings have implications for the introduction of the European Deposits Insurance Scheme (EDIS), for which they offer tentative support.
Keywords: F30; F36; F45; G11; G15; 330; private bank deposits; macro; fiscal risk; Eurozone; TVP panel; fragmentation